2015
DOI: 10.1152/ajpheart.00850.2014
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 mediates exercise preconditioning against myocardial ischemia reperfusion injury

Abstract: Interleukin-6 (IL-6) is a pleiotropic cytokine that protects against cardiac ischemia-reperfusion (I/R) injury following pharmacological and ischemic preconditioning (IPC), but the affiliated role in exercise preconditioning is unknown. Our study purpose was to characterize exercise-induced IL-6 cardiac signaling (aim 1) and evaluate myocardial preconditioning (aim 2). In aim 1, C57 and IL-6(-/-) mice underwent 3 days of treadmill exercise for 60 min/day at 18 m/min. Serum, gastrocnemius, and heart were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 61 publications
(71 reference statements)
4
65
2
Order By: Relevance
“…Previous researchers suggest that aerobic exercise can provoke an IL-6 response from muscle cells, and this finding may be associated with exercise-associated metabolic changes, adaptation to training, and possibly preconditioning individuals against myocardial ischemia-reperfusion injury [9, 11, 13]. It has further been proposed that such responses can be related to the intensity of the exercise and mediate both autocrine and paracrine benefits of training [9, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous researchers suggest that aerobic exercise can provoke an IL-6 response from muscle cells, and this finding may be associated with exercise-associated metabolic changes, adaptation to training, and possibly preconditioning individuals against myocardial ischemia-reperfusion injury [9, 11, 13]. It has further been proposed that such responses can be related to the intensity of the exercise and mediate both autocrine and paracrine benefits of training [9, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Such remarkable findings could signify that keeping our skeletal muscles in good shape helps our myocardium in its cardioprotective aspect via elevation of circulating IL-6. 34 Somewhat in line with the findings of McGinnis et al, it was revealed that if ischemia/reperfusion events are triggered in a remote organ, the myocardium can acquire a higher resistance to ischemic injury as a result. 34,35 Under remote ischemic preconditioning (RIPC), there was decrease of serum troponin I levels with an accompanying increase of STAT5 phosphorylation in patients undergoing coronary artery bypass surgery in comparison with control patients without RIPC.…”
Section: The Therapeutic Implications Of Stat Proteins -Current Statementioning
confidence: 54%
“…34 Somewhat in line with the findings of McGinnis et al, it was revealed that if ischemia/reperfusion events are triggered in a remote organ, the myocardium can acquire a higher resistance to ischemic injury as a result. 34,35 Under remote ischemic preconditioning (RIPC), there was decrease of serum troponin I levels with an accompanying increase of STAT5 phosphorylation in patients undergoing coronary artery bypass surgery in comparison with control patients without RIPC. 35 In a pig experimental model of remote ischemic preconditioning, it was proved that RIPC limited infarct size and augmented STAT3 phosphorylation while STAT5 remained decreased in the early phase of reperfusion in both the RIPC and control groups.…”
Section: The Therapeutic Implications Of Stat Proteins -Current Statementioning
confidence: 54%
See 2 more Smart Citations